2014
DOI: 10.1002/nur.21608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Three-Month Therapeutic Lifestyle Modification Program to Improve Bone Health in Postmenopausal Korean Women in a Rural Community: A Randomized Controlled Trial

Abstract: In this randomized controlled trial, we examined the effects of a 3-month therapeutic lifestyle modification (TLM) intervention on knowledge, self-efficacy, and health behaviors related to bone health in postmenopausal women in rural Korea. Forty-one women ages 45 or older were randomly assigned to either the intervention (n = 21) or control (n = 20) group. The intervention group completed a 12-week, 24-session TLM program of individualized health monitoring, group health education, exercise, and calcium-vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…The present study demonstrates that even though serum NTX levels were not decreased by combined exercise, there were significant increases in the serum sALP levels, showing the potential for combined exercise to positively affect bone quality in postmenopausal women. Previous studies have shown the positive effect of exercise on bone health in post-menopausal women, usually by a reduction in bone loss [22]. The participants of this study did not always show extremely high bone turnover.…”
Section: Discussionmentioning
confidence: 41%
“…The present study demonstrates that even though serum NTX levels were not decreased by combined exercise, there were significant increases in the serum sALP levels, showing the potential for combined exercise to positively affect bone quality in postmenopausal women. Previous studies have shown the positive effect of exercise on bone health in post-menopausal women, usually by a reduction in bone loss [22]. The participants of this study did not always show extremely high bone turnover.…”
Section: Discussionmentioning
confidence: 41%
“…Numerous studies have investigated the relationship between serum 25(OH)D levels and individual body composition. Calcium and vitamin D were positively associated with bone health in several studies . A study involving a nationwide sample of Koreans aged 40 years and older showed a lower mean value of appendicular skeletal muscle mass index (ASSMI) in men, but not in women, with hypovitaminosis, defined as serum 25(OH)D < 20 ng/mL .…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Previous studies have indicated a significant association between serum vitamin D and individual components of abnormal body composition, manifesting as osteoporosis, sarcopenia, and obesity. [10][11][12][13][14][15][16] Besides vitamin D having individual protective effects on either bone or muscle mass and modulating body fat accumulation, 7,8,[17][18][19] vitamin D as a single factor displaying combined effects, such as on both bone and muscle mass, has been suggested. 12 However, few studies have examined the relationship between serum vitamin D with combined abnormalities in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about whether such interventions affect patient satisfaction or QOL [17, 18]. Most of these RCTs examining OP patient-education interventions have been multifaceted or lengthy [7, 12, 13, 15, 16], which are not scalable. To date, only one RCT has examined the effect of an OP education intervention on QOL, reporting a beneficial effect after both three months and one year [16].…”
Section: Introductionmentioning
confidence: 99%